Sex-dependent novelty response in neurexin-1α mutant mice. - Marijke C Laarakker; Niels R Reinders; Hilgo Bruining; Roel A Ophoff; Martien J H Kas (PLoS ONE, 2012)
Neurexin-1 alpha (NRXN1α) belongs to the family of cell adhesion molecules (CAMs), which are involved in the formation of neuronal networks and synapses. NRXN1α gene mutations have been identified in neuropsychiatric diseases including Schizophrenia (SCZ) and Autism Spectrum Disorder (ASD). In order to get a better understanding of the pleiotropic behavioral manifestations caused by NRXN1α gene mutations, we performed a behavioral study of Nrxn1α heterozygous knock-out (+/-) mice and observed increased responsiveness to novelty and accelerated habituation to novel environments compared to wild type (+/+) litter-mates. However, this effect was mainly observed in male mice, strongly suggesting that gender-specific mechanisms play an important role in Nrxn1α-induced phenotypes.